PSXVI-12 Revolutionizing in vitro endometrial cell studies: A novel methodology to obtain bovine endometrial cells. (8th October 2021) - Rocha, Cecilia Constantino; da Silva, Felipe Alves Correa Carvalho; Martins, Thiago; Marrero, Marcela; Driver, John; Bromfield, John; Hansen, Thomas (Tod) R; Binelli, Mario
Abstract: Cultured primary endometrial cells are used extensively to study uterine function in cattle. However, most protocols harvest endometrial cells from slaughtered animals at estimated stages of the estrous cycle. The goal of this study was to establish and validate an in vivo, minimally invasive, and estrous cycle stage-specific method to obtain endometrial cells for culture. In Experiment 1, the uterine body of Bos indicus-influenced cows was sampled using a cytology brush (cytobrush) 4 days post estrus (D4; n = 13). Brushes were transported in medium (DMEM/F12, 3% Penicillin/Streptomycin and 2% of Fungizone) to the laboratory at ambient temperature. Cells were cultured in medium containing 10% FBS at 5% of CO2 (38°C). Confluent cells (~7 days of culture) were sub-cultured for two subsequent passages. Pools (n = 4) of cells from 2–3 animals, were frozen, thawed, and re-plated (passage 3). The relative transcript abundance of PPIA, ACTB, KRT18, VIM, OXTR, PGR, ESR1 and IFNAR1 were analyzed by qPCR and compared among fresh cells and cells from each passage. Abundance of KRT18 and VIM transcripts was similar across passages, while PGR, ESR1, OXTR and IFNAR1 transcripts decreased by 90, 96, 84, and 82 %; respectively in cultured compared to fresh cells (P < 0.05). In Experiment 2, passage 3 cells were cultured for 24 hours with 0 or 1ng/mL of recombinant bovine interferon-tau (rbIFNT; n = 3 replicates/treatment). The relative expression of a classical interferon stimulated gene, ISG15, was evaluated by qPCR. Expression of ISG15 was 6-fold greater (P < 0.05) in the rbIFNT treated cells compared to controls. In conclusion, the culture of endometrial cells collected by cytobrush is feasible, generates a monolayer enriched in epithelial cells and may be used as a model for physiological studies involving IFNT signaling. Further experiments to ascertain the physiological relevance of this model are underway.